Technological Eco-Innovations for the Quality Control and the Decontamination of Polluted Waters and Soils - Zacchini, Massimo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Special Issue "Technological Eco-Innovations for the Quality Control and the Decontamination of Polluted Waters and Soils" deals with the most recent research activities carried out at lab and field scale on eco-sustainable tools for the remediation of contaminated environmental substrates. It is particularly devoted to highlight the relevance of biological organisms (plants, microbes, algae) to assess the chemical contamination in water and soil and to remediate such matrices from the pollution caused by the human activities. Therefore, bioremediation is a primary focus of most of the articles published within the present Special Issue. Bioremediation is a promising environmentally friendly technology to deal with the chemical pollution in different ecosystem compartments and its integration with the traditional approaches might represent a